Efektivitas Penggunaan Bahan Ajar Kalkulus Berbasis ICT Terintegrasi Masalah Kontekstual untuk Meningkatkan Aktivitas, Motivasi, dan Hasil Belajar Mahasiswa - Dewi Murni; Helma Helma; Mirna Mirna (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
This research is part of the development research on Calculus teaching materials. The purpose of this study was to see the effectiveness of using Technology Information Comunication-based calculus teaching materials integrated contextual issues, especially to find out the activities and motivation of student learning while using the calculus teaching materials. Instruments for collecting data in research observation sheets and questionnaires. The data analysis technique used is descriptive statistical analysis. The results of the study are teaching materials Calculus can activate students in lectures and increase students' skills in utilizing information technology progress and can increase learning motivation, student perseverance and enthusiasm in Calculus lectures.